Pengaruh Ukuran Perusahan, Leverage, dan Profitabilitas terhadap Penghindaran Pajak pada Perusahaan Sub-Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Putri Agil Vionyca; Desy Ismah Anggraini (Teewan Journal Solutions, 2025)
Taxes are one of the sources of state revenue used to finance the country’s needs for the benefit of society. However, in practice, many business entities seek to minimize the amount of taxes paid through tax avoidance strategies. This study aims to analyze the effect of firm size, leverage, and profitability on tax avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2022–2024. The study uses a quantitative approach with multiple linear regression analysis. The sample consists of 15 companies selected using purposive sampling, with secondary data obtained from annual financial reports over three years. The results show that simultaneously, firm size, leverage, and profitability significantly influence tax avoidance. Partially, only profitability has a positive and significant effect on tax avoidance, while firm size and leverage show no significant influence. These findings indicate that the higher a company’s profitability, the greater its tendency to engage in tax avoidance.